2017
DOI: 10.1016/j.ajic.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

No bacterial growth found in spiked intravenous fluids over an 8-hour period

Abstract: Protocol changes prompted by the Joint Commission mandating intravenous (IV) fluid bags to be used within 1 hour of spiking because of possible bacterial contamination have sparked clinical and economic concerns. This study investigated the degree of bacterial growth in which samples were obtained from spiked IV fluid bags at the time of spiking and 1, 2, 4, and 8 hours after spiking. No bacterial growth occurred in any of the 80 bags of Lactated Ringer's (LR) IV solutions sampled. This study demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Scientific literature pertaining to spiking IV bags is sparse. Haas et al 41 found no bacterial growth up to 8 hours in 80 bags of lactated Ringer’s solution spiked by a single provider following proper HH, but they did not address whether these results are replicable across multiple providers, in other settings, and with other types of IV solutions.…”
Section: How Long Can IV Bags Be Spiked In Advance Of Commencing Use?mentioning
confidence: 98%
“…Scientific literature pertaining to spiking IV bags is sparse. Haas et al 41 found no bacterial growth up to 8 hours in 80 bags of lactated Ringer’s solution spiked by a single provider following proper HH, but they did not address whether these results are replicable across multiple providers, in other settings, and with other types of IV solutions.…”
Section: How Long Can IV Bags Be Spiked In Advance Of Commencing Use?mentioning
confidence: 98%
“…Este estudio simulaba la práctica clínica habitual de reutilizar las bolsas de soluciones intravenosas, y se colocaron el área de hospitalización que es el lugar donde es más frecuente su uso y administración a pacientes. Las investigaciones en Medicina Humana sobre la contaminación de las soluciones intravenosas son escasas y en Medicina Veterinaria no existen [9,10,16]. En 1971 el CDC emitió una guía para el manejo de las soluciones y recomienda el descarte de las bolsas a las 24 h; desde esa fecha no se ha actualizado la guía para su manejo [3,6,17].…”
Section: Cloruro Deunclassified
“…Zu dieser Fragestellung existiert wenig Literatur. In einer Studie wurde festgestellt, dass innerhalb von 8 h nach dem Anstechen von insgesamt 80 Ringer-Lactat-Infusionen, die von Fachpersonal nach dem Durchführen einer hygienischen Händedesinfektion vorbereitet wurden, kein Bakterienwachstum nachweisbar war [ 31 ]. Allerdings lässt diese Studie keine Rückschlüsse darauf zu, ob dies auch für andere Infusionen in anderen Szenarien gültig ist.…”
Section: Wie Lange Vor Gebrauch Dürfen Infusionen Angestochen Werden?unclassified